2000
DOI: 10.1287/opre.48.5.801.12407
|View full text |Cite
|
Sign up to set email alerts
|

A Lower Bound for the Split Delivery Vehicle Routing Problem

Abstract: In this paper we consider the Split Delivery Vehicle Routing Problem (SDVRP), a relaxation of the known Capacitated Vehicle Routing Problem (CVRP) in which the demand of any client can be serviced by more than one vehicle. We define a feasible solution of this problem, and we show that the convex hull of the associated incidence vectors is a polyhedron (PSDVRP), whose dimension depends on whether a vehicle visiting a client must service, or not, at least one unit of the client demand. From a partial and linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 17 publications
0
136
0
2
Order By: Relevance
“…The column generation algorithm is able to obtain gaps (UB − LB)/U B, which are consistently smaller than those generated by Belenguer et al [4].…”
Section: Column Generationmentioning
confidence: 65%
See 2 more Smart Citations
“…The column generation algorithm is able to obtain gaps (UB − LB)/U B, which are consistently smaller than those generated by Belenguer et al [4].…”
Section: Column Generationmentioning
confidence: 65%
“…The proposed column generation algorithm is tested on 11 problem instances and compared with the cutting plane approach of Belenguer et al [4]. The column generation algorithm is able to obtain gaps (UB − LB)/U B, which are consistently smaller than those generated by Belenguer et al [4].…”
Section: Column Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…They solved its LP relaxation using column generation and applied a rounding method to get a feasible IP solution. Belenguer et al (2000) studied the polyhedron of SDVRP and identified some facets of it. Using corresponding valid inequalities, they developed a cuttingplane algorithm to generate the lower bound of the optimal value.…”
Section: Split Delivery Vehicle Routing Problemmentioning
confidence: 99%
“…The procedure was tested on three small instances up to 20 clients and varying client demands. The SDVRP was studied from a polyhedral point of view in [5]. Based on the partial description of the SDVRP polyhedron, the same authors implemented a branch and cut algorithm capable of solving some medium size instances up to 51 clients.…”
Section: Introductionmentioning
confidence: 99%